Viral infections in cancer patients at the stages of antitumor treatment - T. A. Zykova; D. A. Rozenko; N. N. Popova; E. A. Solovova; Yu. Yu. Kozel; A. V. Shulga (Южно-Российский онкологический журнал, 2025)
Purpose of the study. To analyze cases of viral infection in cancer patients at the stages of antitumor therapy.Patients and methods. We conducted a retrospective analysis of the medical histories of 50 patients with acute respiratory failure (I–III st.), hospitalized in the Department of anesthesiology and intensive care in 2017–2020. Of these, 34 are children and 16 are adults. Sputum, tracheobronchial aspirate, and blood were examined for the presence of viral agents.Results. Viral infection was confirmed in 35 (70 %) patients. During CT, it developed more often than in the early postoperative period (72.2 % vs 64.3 %, p > 0.05), but this situation is true only for the general group of patients. In children, viral infection was diagnosed only on CT (71.9 % of those receiving CT, p = 0.098, F = 0.13), and in adults it was equally common (75 % each), both during CT and after surgery. In lung cancer, viral infection was confirmed in 7 (100 %), pelvic fever in 7 (63.6 %), bones, connective and soft tissues in 6 (66.7 %), hemoblastoses in 3 (75 %), central nervous system tumors in 5 (71.4 %) patients. Herpesvirus infection (HVI) was confirmed in 15 (42.9 % of the infected), respiratory viral infection (RVI) in 13 (37.1 %), and their combination in 7 (20 %) patients. In general, we note a slight predominance of HVI over RVI (22/62.9 % vs. 20/57.1 %, p > 0.05). Mixed infection with a combination of two to four pathogens and mono-infection developed equally frequently: in 18 (51.4 %) and 17 (48.6 %) patients, respectively.Conclusions. Infectious complications are an important component of modern antitumor treatment. Therefore, it is necessary to monitor the spectrum of viral infections in cancer patients with signs of respiratory dysfunction at the stages of antitumor therapy. Proper assessment of the situation will help to avoid the development of critical consequences, reduce the time of hospitalization, and improve the course and prognosis of cancer.